Engaged sustainability science and place-based transgressive learning in higher education - Lotz-Sisitka, Heila; le Grange, Lesley; Mphepo, Gibson (South African Journal of Science, 2024)
This article is located within current debates on engaged science and learning in higher education, with emphasis on types of learning emerging from engaged sustainability science, and associated contributions to debates on decoloniality in higher education. In particular, the article deliberates how a focus on sustainability science practised as place-based transgressive learning can add to debates on decoloniality in higher education. Through analysis of two case studies, we propose that co-engaged place-based research and learning emerges as a form of multi-loop, transgressive learning that offers possibilities for advancing understanding of decolonising learning processes, at least in those parts of the higher education system where the learning and sustainability sciences meet. This is offered as an approach to deepen science engagement in contemporary African contexts. Significance: • The article offers insight into how science engagement practised as place-based, transgressive learning can contribute to decolonisation of higher education, especially through learning processes. • It draws on insight from the learning sciences (notably Bateson’s work on single, double and triple loop learning, but also theory from decolonial, expansive and transgressive learning) and shows how this can deepen understandings of science engagement practised as place-based transgressive learning.